Synthesis, Characterization of Novel Azo Compounds as Corrosion Inhibitors for Carbon Steel in HCl, and Their Theoretical Study - Jarallah, Hanadi M.; Dhaef, Hawraa Kareem; Mohammed, Mohammed K.; Ismal, Sadiq M. H.; Hussein, Ala’a Ali (Science and Technology Indonesia, 2026)
Two azo compounds were produced, and their chemical properties were validated using spectroscopic methods (mass and 1H NMR). A potential dynamic polarization approach was employed to evaluate the synthesized derivatives as corrosionreducing materials for carbon steel in a 1 M HCl solution. The derived products, (E)-4-((3-(tert-butyl)-2-hydroxy-5-methoxyphenyl)diazenyl)-N-(5-methylisoxazol-3-yl)benzenesulfonamide (I) and (E)-4-((2-hydroxynaphthalen-1-yl)diazenyl)-N-(5-methylisoxazol-3-yl)benzenesulfonamide (II) achieved 89.9% and 83.02% inhibition rates at 5 × 10−3 M concentrations, Langmuir was aligned with the isotherm adsorptions of these materials. Density functional theory was employed to assess the quantum chemical characteristics of azo-based inhibitors. A conceptual assessment was performed using DFT/B3LYP 6-311+G (d,p) to evaluate the structure of the molecule, its physical and chemical properties, and the electronic factors that impact its inhibitory significance. The DFT outcomes were aligned with the practical records.